The role of preoperative transfusion in sickle cell disease, a systematic review and meta-analysis - Yasamin Abdu (15899155) (2024)
This systematic review and meta-analysis aimed to provide guidance on preoperative blood transfusion strategies for patients with sickle cell disease (SCD). We included all randomized controlled and observational studies exploring the clinical outcomes of preoperative blood transfusion among patients with SCD compared to the conservative transfusion strategy until 14/09/2022. Sixteen studies involving 3486 participants were analysed. The findings revealed a significantly higher bleeding rate in patients who received preoperative transfusion than those who followed a conservative strategy (RR = 4.32, 95% CI 1.75–10.68, P = 0.002, I2 = 0%). However, the two strategies had no significant differences in other clinical outcomes, such as acute chest syndrome, painful crisis, fever, neurological complications, thrombosis, ICU admission, and mortality. It is important to note that all the included studies had a moderate risk of bias. Preoperative transfusion in SCD was associated with a higher bleeding risk but a similar risk in other outcomes compared to conservative strategies. Notably, the increased bleeding risk observed seldom had clinical significance. We recommend individualizing management strategies, considering the overall positive impact of transfusions in reducing complications. Further high-quality studies are needed to refine recommendations. Other Information Published in: Blood Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.blre.2024.101183